Perancangan Strategi Branding dan Social Media Marketing Pada Toko Crystalnkiss - Kesumahati, Erilia; Jecki, Jecki (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Crystalnkiss shop is a Micro, Small and Medium Enterprise (MSME) in Batam City that sells various clothes imported from China and Thailand. Sales from this store continue to decline even though COVID-19 has passed. Digital marketing carried out on social media has not provided satisfactory results. Thus, community service activities were carried out to increase sales by implementing branding strategies and conducting social media marketing. Promotional activities are carried out using social media, marketplaces, and registration of store locations on Google Map. The implementation results show business progress in terms of increasing the number of customers and sales.